TRAIL/Apo-2L: Mechanisms and Clinical Applications in Cancer - Rakesh K. Srivastava (Neoplasia: An International Journal for Oncology Research, 2001)
TNF-related apoptosis-inducing ligand (TRAIL/APO2L) is a member of the TNF family that promotes apoptosis by binding to the transmembrane receptors TRAIL-R1 /DR4 and TRAIL-R2/DR5. Its cytotoxic activity is relatively selective to the human tumor cell lines without much effect on the normal cells. Hence, it exerts an antitumor activity without causing toxicity, as apparent by studies with several xenograft models. This review discusses the intracellular mechanisms by which TRAIL induces apoptosis. The major pathway of its action proceeds through the formation of DISC and activation of caspase-8. The apoptotic processes, therefore, follow two signaling pathways, namely the mitochondrial-independent activation of caspase-3, mitochondrial-dependent apoptosis due to cleavage of BID by caspase-8, the formation of apoptosomes, activation of caspase-9 and the downstream caspases. Bcl-2 and Bcl-XL have no effect on TRAILinduced apoptosis in lymphoid cells, whereas these genes block or delay apoptosis in nonlymphoid cancer cells. TRAIL participates in cytotoxicity mediated by activated NK cells, monocytes, some cytotoxic T cells. Hence, TRAIL may prove to be an effective antitumor agent. In addition, it may enhance the effectiveness of treatment with chemotherapeutic drugs and irradiation. Nontagged Apo-2L/TRAIL does not cause hepatotoxicity in monkeys and chimpanzees and in normal human hepatocytes. Thus, nontagged Apo-2L/TRAIL appears to be a promising new candidate for use in the treatment of cancer. Neoplasia. (2001)